Functional Crypto-Adenylate Cyclases Operate in Complex Plant Proteins - Al-Younis, Inas; Moosa, Basem; Kwiatkowski, Mateusz; Jaworski, Krzysztof; Wong, Aloysius; Gehring, Chris (Frontiers in Plant Science, 2021)
Adenylyl cyclases (ACs) and their catalytic product cAMP are regulatory components of many plant responses. Here we show that an amino acid search motif based on annotated adenylate cyclases (ACs) identifies 12 unique Arabidopsis thaliana candidate ACs, four of which have a role in the biosynthesis of the stress hormone abscisic acid (ABA). One of these, the 9-cis-epoxycarotenoid dioxygenase (NCED3, At3g14440), was identified by sequence and structural analysis as a putative AC and then tested experimentally with two different methods. Given that the in vitro activity is low (fmoles cAMP pmol-1 protein min-1), but highly reproducible, we term the enzyme a crypto-AC. Our results are consistent with a role for ACs with low activity in multi-domain moonlighting proteins that have at least one other distinct molecular function such as catalysis or ion channel activation. We propose that crypto-ACs be examined from the perspective, that their low activities are an innate feature of regulatory ACs embedded within multi-domain moonlighting proteins. It is therefore conceivable that crypto-ACs form integral components of complex plant proteins participating in intramolecular regulatory mechanisms, and in this case, potentially linking cAMP to ABA synthesis.